Coopetitive networks in the ICT sector. (28th January 2008) - Ritala, Paavo; Hallikas, Jukka; Sissonen, Heli
This paper provides evidence of simultaneous competition and cooperation (coopetition) through analysing the centrality measures of a set of global Information and Communication Technology (ICT) companies in competitive and cooperative networks. We use structural network research and the Ucinet program as tools for identifying the centrality of the companies in these networks. These data are compared with the absolute number of simultaneously cooperative and competitive relationships announced in the firms' annual reports and on the alliance database (SDC Platinum). Our study predicts that centrality in both competitive and cooperative networks, and in particular high centrality in the cooperative network, indicates higher levels of coopetition. This indicates the importance of alliance management in this context. We also find that firms with a niche focus are less likely to form coopetitive relationships. Finally, our study illustrates that structural analysis is suitable for analysing coopetition at the network level.